Evaluasi Pengaturan Kelembagaan Kawasan Ekonomi Khusus di Indonesia - Muh Ali Masnun; Eny Sulistyowati; Mahendra Wardhana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2021)
This study aims to analyze / evaluate the institutional arrangements for SEZs in Indonesia, particularly the formulation of the composition of the Dewan Kawasan and the provisions for determining strategic steps for problems experienced by SEZs. The research method used is normative research supported by primary and secondary legal materials with prescriptive analysis. The results showed that the institutional arrangements for the Special Economic Zone for the composition of the Dewan Kawasan are still blurred (in terms of quality and quantity) and need interpretation. The meaning of the representative of the Government means that power is the authority of the Central Government. The Government Representative in the determination to be part of the Dewan Kawasan needs to regard to the main activities that are developed, so that the management of SEZs can be managed professionally and able to achieve the mandate of the constitution to advance public welfare. Artikel ini bertujuan untuk menganalisis/mengevaluasi pengaturan kelembagaan KEK di Indonesia, khususnya formulasi komposisi Dewan Kawasan dan ketentuan penetapan langkah strategis atas permasalahan yang dialami sebuah KEK. Penelitian ini menggunakan penelitian normatif dengan ditunjang dengan bahan hukum primer dan sekunder dengan analisis preskriptif. Hasil penelitian menunjukkan bahwa pengaturan kelembagaaan Kawasan Ekonomi Khusus untuk komposisi Dewan Kawasan masih kabur (dari sisi kualitas maupun kuantitas) dan perlu penafsiran. Makna wakil Pemerintah berarti adalah kekuasaan yang menjadi kewenangan Pemerintah Pusat. Wakil Pemerintah dalam penentuan menjadi bagian dari Dewan Kawasan perlu memperhatikan kegiatan utama yang dikembangkan, sehingga pengelolaan KEK dapat dikelola secara professional dan mampu mencapai amanah konstitusi untuk memajukan kesejahteraan umum.